1990
DOI: 10.1002/jrs.1250211107
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and reaction of 4‐methoxycinnamonitrile on a silver surface: A surface‐enhanced Raman spectroscopic study

Abstract: Surface-enhanced Raman scattering of cis-and trans-Qmethoxycinnamonitrile (4MCN) was investigated in aqueous silver sols. Both isomers adsorbed on the silver surface via the cyano group. The adsorption strength for the cis isomer appeared to be greater than that for the trans isomer. However, cis-4MCN, adsorbed selectively on the silver surface, was readily converted to the trans isomer via a laser-assisted surface reaction. The exact mechanism of the photoisomerization is not yet completely understood. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Comparison with Nitriles. In organometallic chemistry, nitriles are generally known to have a σ-type coordination to metal atoms via the nitrogen lone-pair electrons. , The compiled SERS data ,− of various aromatic nitriles, however, have led a conclusion that a majority of aromatic nitriles were adsorbed on the silver surface via C⋮N π system by referring to the spectral shifts of the ν(CN) bands.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with Nitriles. In organometallic chemistry, nitriles are generally known to have a σ-type coordination to metal atoms via the nitrogen lone-pair electrons. , The compiled SERS data ,− of various aromatic nitriles, however, have led a conclusion that a majority of aromatic nitriles were adsorbed on the silver surface via C⋮N π system by referring to the spectral shifts of the ν(CN) bands.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has extended the study to formic, acetic, propionic, butyric and acrylic acids and some of their derivatives and it was found that some of them show systematically what we called an anomalous SERS spectrum, independently of the nature of the adsorbate. 18,19 In this respect, many SERS studies have shown chemical transformations such as polymerizations, 6,20 isomerizations, 21 photodecompositions 22 and even hydrolysis reactions. 23 The aforementioned studies were conducted from the point of view of the electromagnetic enhancement mechanism (EM), which allows us to derive the orientation of the adsorbate on the basis of the relevant selection rules.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of metal−nitrile complexes has attracted much attention in view of the fact that the −C⋮N: group is isoelectronic with molecular nitrogen and that organonitrile complexes can serve as convenient precursors for a wide variety of coordination complexes . In organometallic chemistry, nitriles are generally known to coordinate to metal atoms via the nitrogen lone-pair electrons. , In our previous surface-enhanced Raman scattering (SERS) studies of various nitriles in silver sols, a majority of aromatic nitriles were found, however, to adsorb via the C⋮N π system rather than the nitrogen lone-pair electrons. Thereby, for 1,4-dicyanobenzene (1,4-DCB), both of the nitrile groups seemed to interact effectively with the silver surface via their π systems, assuming a flat molecular orientation with respect to the surface.…”
Section: Introductionmentioning
confidence: 99%